2010
DOI: 10.1097/jto.0b013e3181c8cc0c
|View full text |Cite
|
Sign up to set email alerts
|

TGF-² Signaling Pathway in Lung Adenocarcinoma Invasion

Abstract: The histological distinction between bronchioloalveolar carcinoma (BAC) and other adenocarcinomas is tissue invasion. The clinical importance of lung adenocarcinoma invasion is supported by several recent studies indicating that the risk of death in non-mucinous BAC is significantly lower than that of pure invasive tumors and in tumors with greater than 0.6 cm of fibrosis or linear invasion. Using microarray gene expression profiling of human tumors, dysregulation of transforming growth factor-ß (TGF-ß) signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 76 publications
0
45
0
1
Order By: Relevance
“…Ras pathway mutation classically activates growth factors including transforming growth factor beta (TGF-b), which induces ZEB1 mRNA, represses Pten mRNA and causes cell proliferation (Supplementary Fig. 6; refs [24][25][26]. Thus, release of growth factors such as TGF-b from K-Ras mutant tumours might be sufficient for ZEB1 induction, PTEN repression and proliferation of tumour-associated fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Ras pathway mutation classically activates growth factors including transforming growth factor beta (TGF-b), which induces ZEB1 mRNA, represses Pten mRNA and causes cell proliferation (Supplementary Fig. 6; refs [24][25][26]. Thus, release of growth factors such as TGF-b from K-Ras mutant tumours might be sufficient for ZEB1 induction, PTEN repression and proliferation of tumour-associated fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Destruction of TGF-β signaling (especially TGFβRII) clearly induces tumorigenicity (28). However, tumors frequently lose their negative growth response to TGF-β and, in contrast, TGF-β signaling may promote tumor cell invasion and metastasis due to its ability to stimulate angiogenesis, alter the stromal environment, and significantly, cause local and systemic immunosuppression (8,(28)(29)(30)(31). Since it is still unclear as to whether TGF-β signaling plays a biological role in LAC progression, we focused on TGFβRII knockdown in LAC cells A549 to investigate the anti-tumor function of TGFβRII in vitro using RNA interference.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β binds to TGF-β receptor, type II (TGFβRII), which then phosphorylates and activates the type I receptor in the complex, and activates SMAD-dependent and -independent pathways. The non-SMAD signaling pathways are likely to mediate the positive effects on pro-carcinogenesis (6)(7)(8). Several investigators have reported that inactivation of the TGF-β signaling pathway reduces the ability of human cancer cells to progress (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Действитель-но, при НМРЛ -наиболее распространенном гисто-логическом подтипе РЛ с высоким уровнем смертно-сти -увеличение экспрессии TGF-β1 коррелирует с прогрессией опухоли и плохой выживаемостью па-циентов. Различные экспериментальные модельные системы подтверждают мнение о прометастатической роли TGF-β1 в этих опухолях [22][23][24][25]. Тем не менее одной из основных нерешенных задач остается иден-тификация генов-мишеней для TGF-β1, которые управляют различными стадиями метастазирования, тем более что TGF-β1 модулирует экспрессию генов по-разному в зависимости от типа клеток [26,27].…”
Section: Discussionunclassified